Reflectance - Current state of research and future directions for archaeological charcoal; Results from a pilot study on Irish Bronze Age cremation charcoals. (November 2016) - Veal, Robyn; O'Donnell, Lorna; McParland, Laura
Abstract: 'Reflectance' is a method that estimates the absolute burn temperature of charcoal from the 'shininess' of resin mounted samples. The method's usefulness for archaeological charcoal is yet to be comprehensively studied. This article details first results from reflectance testing of archaeological charcoals excavated from Irish Bronze Age cremations, which included calcined bone. As calcination of bone commences at 650 °C, it was expected that the charcoals would reflect at least this temperature. This was not the case for taxonomically identified charcoals >2 mm, nor for micro-charcoals of c. 250 μm, although measured temperatures rose slightly with decreasing fraction size of charcoal remains. Depositional practice, combustion completeness and taphonomic influences may have all played a part in this result, and these will need careful consideration in different archaeological circumstances. However, the greatest challenge for reflectance of archaeological materials lies in obtaining full agreement on the production and use of reflectance calibration curves. Current calibration curves differ substantially, by 100–150 °C ( ±50–75 °C) and in one instance up to as much as 180 °C ( ±90 °C). Without better agreement on calibration, the method's ultimate usefulness in archaeological research will be limited. At the level of refinement currently possible, it will still be useful for determining very high or very low temperature processes, and possibly the difference between charcoal fuel and raw wood fuel fires. The latter has distinct implications for estimating ancient forest wood consumption, since more wood is consumed in processes employing charcoal fuel. Proving the utility of reflectance for archaeological purposes may also require modification of normal practice for archaeological field collection of charcoal, to include collection and laboratory processing of un-sieved soil samples. Highlights: This study is the first to use reflectance to measure burn temperatures of charcoal from archaeological cremations. Reflectance shows promise in its application to archaeologically recovered charred materials. Results did not demonstrate the range of expected temperatures associated with cremation (ca. 650 °C up to 1000 °C). Calibration curves need to be rationalised, there is a typical range of variability between 100–150 °C for any one value. Un-sieved soil samples should be collected routinely for this method.